Genetic counseling and testing practices for late-onset neurodegenerative disease: a systematic review - Crook, Ashley (J Neurol, 2021)
OBJECTIVE: To understand contemporary genetic counseling and testing practices for late-onset neurodegenerative diseases (LONDs), and identify whether practices address the internationally accepted goals of genetic counseling: interpretation, counseling, education, and support. METHODS: Four databases were systematically searched for articles published from 2009 to 2020. Peer-reviewed research articles in English that reported research and clinical genetic counseling and testing practices for LONDs were included. A narrative synthesis was conducted to describe different practices and map genetic counseling activities to the goals. Risk of bias was assessed using the Qualsyst tool. The protocol was registered with PROSPERO (CRD42019121421). RESULTS: Sixty-one studies from 68 papers were included. Most papers focused on predictive testing (58/68) and Huntington’s disease (41/68). There was variation between papers in study design, study population, outcomes, interventions, and settings. Although there were commonalities, novel and inconsistent genetic counseling practices were identified. Eighteen papers addressed all four goals of genetic counseling. CONCLUSION: Contemporary genetic counseling and testing practices for LONDs are varied and informed by regional differences and the presence of different health providers. A flexible, multidisciplinary, client- and family-centered care continues to emerge. As genetic testing becomes a routine part of care for patients (and their relatives), health providers must balance their limited time and resources with ensuring clients are safely and effectively counseled, and all four genetic counseling goals are addressed. Areas of further research include diagnostic and reproductive genetic counseling/testing practices, evaluations of novel approaches to care, and the role and use of different health providers in practice. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00415-021-10461-5.